Emotional Intelligence and Psychological Well-Being of Rural Poor School Students In Sabah, Malaysia - Balan Rathakrishnan; Melissa Edora Sanu; Azizi Yahaya; Soon Singh Bikar Singh; Mohammad Rahim Kamaluddin (Psympathic : Jurnal Ilmiah Psikologi, 2019)
Mental health disorders are major causes of disability to those affected, their families and the wider society. Absence of mental illness, or ambitiously, the presence of psychological well-being is key to the optimal functioning of individuals, for them to lead fuller lives and essential for them to contribute actively to society. Some studies have explored the links between psychological well-being and emotional intelligence. However, no such study has focussed on rural, and more often than not, poor students. Our study looked at the effects of emotional intelligence on the psychological well-being of rural poor students in Sabah, Malaysia. It was a cross-sectional study of 430 students. We found that 73% and 90% of the rural students rated their emotional intelligence and psychological well-being as moderate respectively. Regression analysis showed that emotional intelligence could predict one’s psychological well-being. We suggest further research into the differences between school students and school dropouts, and between urban and rural poor students.